Boron deficiency in woody plants: various responses and tolerance mechanisms - Wang, Nannan; Yang, Chengquan; Pan, Zhiyong; Liu, Yongzhong; Peng, Shu’ang (Frontiers in Plant Science, 2015)
Boron (B) is an essential microelement for higher plants, and its deficiency is widespread around the world and constrains the productivity of both agriculture and forestry. In the last decades, accumulating studies on model or herbaceous plants have contributed greatly to our understanding of the complex network of B-deficiency responses and mechanisms for tolerance. In woody plants, however, only a few studies have been conducted and they are not well synthesised. Trees have a larger body size, longer lifespan and more B reserves than do herbaceous plants, indicating that woody species might undergo long-term or mild B deficiency more commonly and that a more complicated B reserves must accordingly be developed to cope with B deficiency. In addition, the highly heterozygous genetic background of tree species suggests that they may have a more complicated mechanism of response and tolerance to B deficiency than do model plants. B-deficient trees usually exhibit two key visible symptoms: depression of growing points (root tip, bud, flower, and young leaf) and deformity of organs (root, shoot, leaf, and fruit). These symptoms may be ascribed to B functioning in the cell wall and membrane, and B deficiency results in damage to vascular tissues and the suppression of both B and water transport. B deficiency also affects metabolic processes, such as increased lignin and phenol, and decreased leaf photosynthesis. These negative effects will influence the quality and quantity of wood, fruit and other agricultural products. B efficiency probably originates from a combined effect of three processes: B uptake, B translocation and retranslocation, and B utilization. Root morphology and mycorrhiza can affect the B uptake efficiency of trees. During B translocation from the root to shoot, differences in B concentration between root cell saps and xylem exudates, as well as water use efficiency, may play key roles in tolerance to B deficiency. In addition, B retranslocation efficiency primarily depends on the ability of xylem-to-phloem transfer and the variety and amount of cis-diol groups. The B requirement for cell construction seems to determine the B use efficiency in trees. Therefore, our review aims to provide an update on the